Functionalized 3D-printed silk-hydroxyapatite scaffolds for enhanced bone regeneration with innervation and vascularization. (September 2021) - Fitzpatrick, Vincent; Martín-Moldes, Zaira; Deck, Anna; Torres-Sanchez, Ruben; Valat, Anne; Cairns, Dana; Li, Chunmei; Kaplan, David L.
Abstract: Our goal was to generate functionalized 3D-printed scaffolds for bone regeneration using silk-hydroxyapatite bone cements and osteoinductive, proangiogenic and neurotrophic growth factors or morphogens for accelerated bone formation. 3D printing was utilized to generate macroporous scaffolds with controlled geometries and architectures that promote osseointegration. We build on the knowledge that the osteoinductive factor Bone Morphogenetic Protein-2 (BMP2) can also positively impact vascularization, Vascular Endothelial Growth Factor (VEGF) can impact osteoblastic differentiation, and that Neural Growth Factor (NGF)-mediated signaling can influence bone regeneration. We assessed functions on the 3D printed construct via the osteogenic differentiation of human mesenchymal stem cells; migration and proliferation of human umbilical vein endothelial cells; and proliferation of human induced neural stem cells. The scaffolds provided mechanical properties suitable for bone and the materials were cytocompatible, osteoconductive and maintained the activity of the morphogens and cytokines. Synergistic outcomes between BMP-2, VEGF and NGF in terms of osteoblastic differentiation in vitro were identified, based on the upregulation of genes associated with osteoblastic differentiation (Runt-related transcription factor-2, Osteopontin, Bone Sialoprotein). Additional studies will be required to assess these scaffold designs in vivo. These results are expected to have a strong impact in bone regeneration in dental, oral and maxillofacial surgery.